Spread of invasive migratory pest Spodoptera frugiperda and management practices throughout China - Yan ZHOU; Qiu-lin WU; Hao-wen ZHANG; Kong-ming WU (Journal of Integrative Agriculture, 2021)
The fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), a notorious migratory pest native to tropical and subtropical America, invaded China in December 2018, then spread through 26 provinces (autonomous regions, municipalities) in 2019 and 27 in 2020, damaging 1.125 and 1.278 million hectares of crops, respectively. Maize was the most severely affected crop, although wheat and other plants were also ruined. Considering the biological characteristics, incidence regularity and migration patterns of the FAW populations, Chinese government implemented a regional control strategy and divided the areas infested with FAW into the annual breeding grounds in Southwest and South China, the transitional migration area in Jiangnan and Jianghuai and the key preventive area in the Huang-Huai-Hai region and North China. The National Agro-Tech Extension and Service Center constructed “the National Information Platform for the Prevention and Control of the Fall Armyworm” at the county level, which would entail people reporting and mapping the spread of fall armyworm. According to forecasting information, millions of extension workers and small-scale growers in entire country were rallied by local governments to fight the pest through comprehensive control tactics including chemical, physical, biological and ecological measures. Thanks to the joint prevention and control, the final loss of crops infested was controlled within 5% of the total in 2019 and 2020. This review also gives a discussion on existing problems and future management scenarios.